Production and Use of Lipases in Bioenergy: A Review from the Feedstocks to Biodiesel Production. (13th June 2011) - Ribeiro, Bernardo Dias; Castro, Aline Machado de; Coelho, Maria Alice Zarur; Freire, Denise Maria Guimarães
Abstract : Lipases represent one of the most reported groups of enzymes for the production of biofuels. They are used for the processing of glycerides and fatty acids for biodiesel (fatty acid alkyl esters) production. This paper presents the main topics of the enzyme-based production of biodiesel, from the feedstocks to the production of enzymes and their application in esterification and transesterification reactions. Growing technologies, such as the use of whole cells as catalysts, are addressed, and as concluding remarks, the advantages, concerns, and future prospects of enzymatic biodiesel are presented.